2007
DOI: 10.1074/jbc.m611365200
|View full text |Cite
|
Sign up to set email alerts
|

Desmoglein Versus Non-desmoglein Signaling in Pemphigus Acantholysis

Abstract: Although it is accepted that pemphigus antibody binding to keratinocytes (KCs) evokes an array of intracellular biochemical events resulting in cell detachment and death, the triggering events remain obscure. It has been postulated that the binding of pemphigus vulgaris IgG (PVIgG) to KCs induces "desmosomal" signaling. Because in contrast to integrins and classical cadherins, desmoglein (Dsg) molecules are not known to elicit intracellular signaling, and because PV patients also produce non-Dsg autoantibodies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
60
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 128 publications
(70 citation statements)
references
References 47 publications
(55 reference statements)
8
60
0
Order By: Relevance
“…Neither antimitochondrial nor anti-Dsg3 antibodies activated the EGFR/Src pathway. This is in keeping with the previous report that gene silencing of Dsg1 and/or Dsg3 via RNA interference does not affect the ability of human KCs to respond to PVIgG by elevation of the EGFR and Src activities (6).…”
Section: Discussionsupporting
confidence: 80%
“…Neither antimitochondrial nor anti-Dsg3 antibodies activated the EGFR/Src pathway. This is in keeping with the previous report that gene silencing of Dsg1 and/or Dsg3 via RNA interference does not affect the ability of human KCs to respond to PVIgG by elevation of the EGFR and Src activities (6).…”
Section: Discussionsupporting
confidence: 80%
“…Interestingly, we found in the present study an up-regulation (calcium channel, voltage-dependent, L type, ␣1D subunit) and down-regulation (gap junction membrane channel protein ␣1) of genes involved in calcium transport. In addition, cell signaling induced by the nondesmoglein autoantibodies produced by PV patients that may target keratinocyte acetylcholine receptors modulates Src and EGF receptor kinase, which have been shown to play an important role in regulation of intracellular adhesion (50). Moreover, we have found recently that PV IgG can recognize an antigen other than desmoglein 3 on peripheral blood mononuclear cell surface (25).…”
Section: Discussionmentioning
confidence: 81%
“…Activation of EGFR due to binding of PV IgG to KCs is followed by phosphorylation of its downstream substrates, the MAPK ERK and the transcription factor c-Jun (18). Although both Src and EGFR kinases contribute to cell shrinkage and keratin filament aggregation, the peak of Src activity precedes that of EGFR kinase (17), indicating that engagement of Src/EGFR may be a key step that relays the signal emanating from interaction of PV IgG with various self-antigens on the keratinocyte plasma membrane to the pathway affecting adhesion complexes. Activation of PKC is also one of the earliest events of PV IgG-induced acantholysis (19).…”
mentioning
confidence: 99%
“…We have previously demonstrated that PV IgG increases the level of phosphorylation of E-cadherin by 42%, ␤-catenin by 37%, ␥-catenin by 136%, and Dsg 3 by 300% (14). Acantholysis caused by pemphigus antibodies can be blocked by inhibitors of protein kinase C (PKC), Src, p38 mitogen-activated protein kinase, epidermal growth factor receptor (EGFR) kinase, other tyrosine kinases and calmodulin (15)(16)(17). Activation of EGFR due to binding of PV IgG to KCs is followed by phosphorylation of its downstream substrates, the MAPK ERK and the transcription factor c-Jun (18).…”
mentioning
confidence: 99%
See 1 more Smart Citation